An Australian Regional Response to Marriage Equality: Newcastle and the Hunter. Issue 11 (19th September 2022) - Betts, David; Bennett, James
ABSTRACT: In Australia same-sex marriage was passed in 2017 following public debates, a postal survey, and legislative reform. This article explores the impact of this process on the rainbow community, with a specific focus on the regional site of Newcastle, New South Wales and the adjacent Hunter Valley. As part of a research project titled "Waiting for Equality, " semi-structured interviews with individuals were conducted that focused on the marriage equality debates, the postal survey and current issues pertaining to equality. The analysis found that the debates and survey exposed many members of the rainbow community to stigma, discrimination, and that there were concerns about how their human rights could be legislatively unwound.